Desempenho Ocupacional de uma criança no Transtorno do Espectro Autista após Terapia Ocupacional Assistida por Cães - Escovar, Bruna Priscila (Universidade Federal de São Carlos, 2024)
Animal-Assisted Therapy (AAT) involves the incorporation of a animal in a therapeutic treatment planned and supervised by a health professional health, such as occupational therapists. TAA includes assessing the needs of the assisted person, definition of objectives, incorporation of the animal in the sessions and monitoring results. In children on Autism Spectrum Disorder (ASD), the TAA with dogs has shown benefits in the development of motor skills, cognitive and psychosocial. Despite the growing international literature, there are still gaps in the definition and evidence on AAT, specifically in Brazil on Therapy Canine-Assisted Occupational. Objectives: Assess and describe problems functions that affect the occupational performance of a child with ASD, develop and implement a Canine-Assisted Occupational Therapy plan for the child, reassess the child and present their reactions and changes in occupational performance after completing 11 TOAC sessions, describe the activities carried out and how the dog was incorporated to achieve therapeutic objectives. Methodology: Single case study method, with intrinsic and qualitative analysis. The participant was a 9-year-old child, diagnosed with ASD and care took place at the School Health Unit of the Federal University of São Carlos. The instruments for data collection were the Canadian Occupational Performance Measure and all sessions were video recorded and later reported with a description of the child's interaction with the dog and therapist, the demonstration of components of occupational performance and engagement during the activity and positive social and emotional behaviors. Result: Comparing pre- and post-intervention results a clinically significant change was observed in the performance of functional problems identified in attention/concentration, pencil grip, scissor grip and activities of daily living involving shoelaces. Based on the child's reactions, engagement in the activities was identified, with the child motivated by the presence of the dog to carry out the activities perseveringly even in the face of difficulty. Discussion: Literature indicates benefits of this type of therapy for children with ASD based on the theory of human-animal interaction (IAH), which suggests that human beings have a natural tendency to form bonds with animals. Conclusion: The proposal for Canine-Assisted Occupational Therapy in this study proved to be beneficial for the child, but as it is a case study it contains limitations, requiring new studies to validate a protocol.
Occupational Performance of a Child on Autism Spectrum Disorder after Canine-Assisted Occupational Therapy
Keywords: Terapia ocupacional; Terapia assistida por animais; Cães; Criança; Transtorno do espectro autista; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL